HUBUNGAN KEPERCAYAAN DIRI DENGAN HASIL BELAJAR DASAR TEKNOLOGI MENJAHIT SISWA KELAS X SMK NEGERI 8 MEDAN - Nurhayati Nurhayati; Zia Ulfa Situmorang (Universitas Negeri Medan, 2017)
ABSTRACT This study aims to: 1) Knowing the level of confidence of students on the basic subjects of sewing technology students class X SMK N 8 Medan.2) To determine whether confidence affects the basic learning outcomes of technology sewing students class X SMK N 8 Medan.3) For Knowing the relationship of confidence to the learning result of basic technology of sewing students of class X SMK N 8 Medan. Technique sample is by using proportional random sampling counted 36 people. For Self Confidence variable (X) data is collected by using questionnaire, while the learning result variable (Y) is crawled by using cognitive test. Data analysis using descriptive, test tendency analysis requirement by using normality test, hypothesis test with product moment correlation. From result of research of student self confidence tends to enough that with percentage 77,8%, so also result of learning base of sewing technology pertained enough with percentage 69 , 4%. Based on the calculation of rxy correlation analysis of 0.719 which means there is a strong relationship between self-confidence with Basic Learning Outcomes Technology Tailoring students class X SMK Negeri 8 Medan. From the result of t-test calculation (significance test) obtained tcount of 6,039 while ttable price with degree of freedom (dk = 36-2 = 34) at 5% significant level is 1,697. And the hypothesis that reads